Construction of some new simple malachite green ion-selective electrodes - Khaled, Elmorsy; Vytřas, Karel; Hassan, Hassan N. A.; Barsoum, Barsoum N. (Univerzita Pardubice, 2002)
The construction and performace characteristics of different types of malachite green ion-selective electrodes are described. These electrodes were prepared either by coating different substrates (metal wires, carbon rode, glass electrode, solid contact electrodes) or like conventional polymeric membrane electrodes with an electroactive material containing malachite green tetraphenylborate ionexchanger and poly(vinyl chloride) plasticized with dibutyl phthalate, or like a carbon paste-based electrode containing the same ion-pair and tricresyl phosphate. Properties of these electrodes were studied. When used for direct potentiometric determination of malachite gree, the electrodes showed Nernstian responses over the concentration range of 1.0x10(-6) - 1.0x10(-3) moll(-1). Their application to the potentiometric titration of malachite green with tetraphenylborate was studied using automated titration mode.
Keywords: iontově selektivní elektrody; malachitová zeleň; membránové elektrody; uhlíkové elektrody; kalibrace; potenciometrická titrace